Sociocultural Appearance Standards and Risk Factors for Eating Disorders in Adolescents and Women of Various Ages - Izydorczyk, Bernadetta; Sitnik-Warchulska, Katarzyna (Frontiers in Psychology, 2018)
The main aim of the present study was to verify the level of impact of sociocultural appearance standards (passive awareness and active internalization) have on body dissatisfaction, the desire to engage in a relentless pursuit of thinness, the adoption of a perfectionistic attitude toward the body, and the development of a tendency to engage in bulimic eating behavior, which can develop in adolescent girls and women of varying ages. The study group comprised 234 individuals: 95 secondary school girls, 33 high school girls, 56 female students, and 50 employed women, all of whom were living in southern Poland. Participants were not diagnosed with any psychiatric disorders (including eating disorders). The variables were measured using the Polish version of Garner’s Eating Disorder Inventory and the Polish Sociocultural Attitudes Towards Physical Appearance and Body Image Inventory [based on the SATAQ-3 (Sociocultural Attitudes Towards Appearance Questionnaire Scale-3)]. The findings revealed that the youngest Polish girls (aged 12–15) reported the highest level of risk factors for eating disorders. Among the entire study group, the internalization of appearance standards and the pressure associated with various media messages were determined to be predictors of the pursuit of thinness, regardless of age and body mass index values. The second most significant variable explained by the internalization of sociocultural standards was body dissatisfaction. The internalization of sociocultural norms provided a significant explanation of bulimic tendencies only in the youngest girls. Perfectionism proved not to be affected by the sociocultural impact of mass media. The adult women had the lowest average scores over the entire study population regarding exposure frequency to body images in mass media and regarding the experience of pressure exerted by sociocultural norms. The high level of internalization of sociocultural appearance standards seems to be significantly linked to body satisfaction in women aged 30 and older. Young adolescent girls constitute a high-risk group for a specific psychological proneness to developing eating disorders as a result of the sociocultural influence exerted by mass media. The obtained study results can prove helpful in creating education programs in preventive healthcare aimed particularly at the youngest adolescents.